Is there an underclass in Britain? - Buckingham, Alan (1999)
This paper sets out to define the underclass and then test the predictions of three competing theories in the underclass debate. Using the National Child Development Study for the analysis it is found that an `underclass' suffering from a lack of qualifications, low cognitive ability and chronic joblessness exists. The validity of making a distinction between the working class and an `underclass' has often been questioned both because of the dubious history of such a distinction and because it is not believed that such a distinction is empirically true. The results in this paper contradict this assertion by finding the underclass to be distinctive from the working class in terms of patterns of family formation, work commitment and political allegiance. The distinct attitudes of the underclass, when coupled with evidence of inter-and intra-generational stability of membership, provide early evidence that a new social class, the underclass, may now exist in Britain. - Reproduced
Keywords: Social class; Disadvantaged groups